Voltage-gated sodium channels and cancer: is excitability their primary role? - Roger, Sébastien; Gillet, Ludovic; Le Guennec, Jean-Yves; Besson, Pierre (Frontiers in Pharmacology, 2015)
Voltage-gated sodium channels (NaV) are molecular characteristics of excitable cells. Their activation, triggered by membrane depolarization, generates transient sodium currents that initiate action potentials in neurons and muscle cells. Sodium currents were discovered by A. Hodgkin and A. Huxley using the voltage clamp technique and reported in their landmark series of papers in 1952. It was only in the 1980's that sodium channel proteins from excitable membranes were molecularly characterized by W. Catterall and his collaborators. Non-excitable cells can also express NaV channels in physiological conditions as well as in pathological conditions. These NaV channels can sustain biological roles that are not related to the generation of action potentials. Interestingly, it is likely that the abnormal expression of Na¬V in pathological tissues can reflect the re-expression of a fetal phenotype. This is especially true in epithelial cancer cells for which these channels have been identified and sodium currents recorded, while it was not the case for cells from the cognate normal tissues. In cancers, the functional activity of NaV appeared to be involved in regulating the proliferative, migrative and invasive properties of cells. This review is aimed at addressing the non-excitable roles of NaV channels with a specific emphasis in the regulation of cancer cell biology.